2019
DOI: 10.1002/anie.201907864
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Thermal Z⇌E Isomerization of a Stable Silene; Experiment and Theory

Abstract: The Ea nd Zg eometric isomers of as table silene (tBu 2 MeSi)(tBuMe 2 Si)Si=CH(1-Ad) (1)were synthesized and characterized spectroscopically.T he thermal Zt oEisomerization of 1 was studied both experimentally and computationally using DFT methods.The measured activation parameters for the 1ZÐ1E isomerization are:E a = 24.4 kcal mol À1 , DH°= 23.7 kcal mol À1 , DS°= À13.2 e.u. Based on comparison of the experimental and DFT calculated (at BP86-D3BJ/def2-TZVP(-f)//BP86-D3BJ/def2-TZVP(-f)) activation parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Very recently, Apeloig et al reported on the synthesis and isomerization of ( E )/( Z )-( t Bu 2 MeSi)­( t BuMe 2 Si)­SiCH­(1-Ad), the first-ever isolable silene stereoisomers . Thus, we conducted further DFT calculations to support the formation of the silenes and especially the assignment of the ( E )/( Z )-isomers.…”
Section: Resultsmentioning
confidence: 77%
“…Very recently, Apeloig et al reported on the synthesis and isomerization of ( E )/( Z )-( t Bu 2 MeSi)­( t BuMe 2 Si)­SiCH­(1-Ad), the first-ever isolable silene stereoisomers . Thus, we conducted further DFT calculations to support the formation of the silenes and especially the assignment of the ( E )/( Z )-isomers.…”
Section: Resultsmentioning
confidence: 77%
“…Consequently, cis -folded isomers of R 2 EER 2 or Z -isomers of REER with heavy main group elements are rare due to increased steric repulsion caused by these substituents. 3 a , b , d ,4…”
Section: Introductionmentioning
confidence: 99%